Polycirridae (Annelida, Terebelliformia) from Lizard Island, Great Barrier Reef, Australia - Nogueira, Joao M. de Matos; Hutchings, Pat A.; Carrerette, Orlemir (Zootaxa, 2015)
In a survey of the polychaetes of the Lizard Island Group, sixteen species of polycirrids were found, from material collected during the two weeks Lizard Island Taxonomic Workshop, together with material collected by previous projects of the Australian Museum based at Lizard Island, including CReefs (http://www.aims.gov.au/creefs/field-program.html). Those species are distributed as follows: two species of Amaeana Hartman, 1959, one new species of Hauchiella Levinsen, 1893, 2 species of Lysilla Malmgren, 1866, one of which is new to science, and 11 species of Polycirrus Grube, 1850, eight of which are new to science. Keys for identification of these genera and species are provided, together with full descriptions for all species, except for those with recent descriptions, and comparisons with the morphologically most similar congeners, in the case of the new species.
World Polychaeta Database (WPolyDb). Open access at Zootaxa